An investigation on the fresh and hardened properties of self-compacting concrete incorporating magnetic water with various pozzolanic materials. (15th January 2018) - Gholhaki, Majid; kheyroddin, Ali; Hajforoush, Mohammad; Kazemi, Mostafa
Highlights: Magnetic water treatment with SF, MK, RHA and FA was found to be suitable for improving flowability. SCC incorporating pozzolanic materials except FA could attain higher viscosity in V-funnel and T 50 tests. SF, MK and FA except RHA caused an increase in compressive and tensile strengths of SCC mixes. SCC containing 20% of SF can be considered as an optimum mix design at the age of 28 days. Absorption characteristics of SCC improve by the inclusion of pozzolanic materials. Abstract: The main objective of this study was to assess engineering properties of self-compacting concrete (SCC) incorporating magnetic water and silica fume, metakaolin, rice husk ash and fly ash (10% and 20% by weight of cement). The fresh properties were investigated by means of slump flow, T50, V-funnel, L-box and visual stability index (VSI). At hardened state, compressive strength was evaluated at the ages of 7 and 28 days and mixes were cast to assess the 28-day splitting tensile strength development and also durability characteristics of concrete were tested for water absorption test at the age of 28 days. Results indicate that magnetic water and pozzolanic materials in SCC can improve the self-compatibility criteria in terms of flowability and viscosity. Furthermore, SCC mixture containing magnetic water and 20% of silica fume can be considered as an optimum mix design at the age of 28 days where compressive strength and splitting tensile strength increased up to 49% and 41%, respectively and the value of water absorption decreased up to 55%. Moreover, magnetic water can reduce the amount of high range water reducer (HRWR), required for SCC, up to 45%.